Case Report: Therapeutic Use of Ibrutinib in a Patient With Schnitzler Syndrome - Huang, Yuehua; Wang, Yanying; Yu, Fan; Mao, Xuehan; Wang, Bianhong; Li, Jingxian; Li, Lihong (Frontiers in Immunology, 2022)
Schnitzler syndrome is a rare adult-onset acquired autoinflammatory disorder typically characterized by chronic urticarial rash and IgM monoclonal gammopathy. Its clinical symptoms are usually well responded to interleukin-1 blockade therapy, which however does not impact the underlying monoclonal gammopathy. Herein, we described a female patient presented with urticarial rash, recurrent fevers, and fatigue for 7 years, and laboratory investigations revealed IgMκ monoclonal protein and MYD88 L265P mutation but no lymphoplasmatic lymphoma on bone marrow examination. She fulfilled the diagnosis of Schnitzler syndrome and was treated with Bruton tyrosine kinase inhibitor ibrutinib in combination with prednisone. Her symptoms improved dramatically and the level of IgMκ monoclonal protein also declined. She tolerated the treatment well. This case highlights the potential therapeutic role of Bruton tyrosine kinase inhibitor in Schnitzler syndrome.